Korup, a case study in forest resource management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
The Korup rainforest of Southwest Cameroon is an area of unique biological diversity. However, hunting and trapping by people living within the protected zone of the Korup National Park, and in the areas immediately outside it, are eliminating many...